One-Pot Synthesis of Hypervalent Diaryl(iodo)bismuthanes from o-Carbonyl Iodoarenes by Zincation. (27th February 2019) - Murafuji, Toshihiro; Hafizur Rahman, A. F. M.; Magarifuchi, Daiki; Narita, Masahiro; Miyakawa, Isamu; Ishiguro, Katsuya; Kamijo, Shin
Abstract : Diaryl(iodo)bismuthanes possessing a hypervalent C=OBi–I bond were conveniently synthesized in a one-pot reaction by using arylzinc reagents generated from o -carbonyl iodobenzenes and zinc powder under ultrasonication. This method is superior to the conventional organolithium and Grignard methods because it has a wide functional group tolerance, requires no protecting group manipulations, and proceeds under mild reaction conditions that do not need low temperature control. Furthermore, no intermediate triarylbismuthane precursor for the hypervalent iodobismuthane is necessary.